2021
DOI: 10.1200/jco.2021.39.15_suppl.4016
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiotherapy to improve overall survival in pancreatic cancer: Long-term results of the multicenter randomized phase III PREOPANC trial.

Abstract: 4016 Background: Preoperative chemoradiotherapy (CRT) may improve overall survival in resectable pancreatic cancer (RPC) and borderline resectable pancreatic cancer (BRPC). Long term results are presented. Methods: In this multicenter phase III trial, patients with RPC or BRPC were randomized between preoperative CRT, (gemcitabine 1000 mg/m2 weekly for 7 of 10 weeks, and 15x2.4 Gy radiotherapy in week 4 to 6), followed by surgery and four cycles of adjuvant gemcitabine (1000 mg/m2 weekly for 3 of 4 weeks), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Even though they didn't reach statistical signi cance in the primary endpoint that was overall survival, a signi cantly higher proportion of patients reached R0 resections in the neoadjuvant arm (71% vs 40%, P<0.001) and also a lower rate of perineural invasion [31]. In a posterior long-term analysis from this trial, three-and ve-year overall survival (intention-to-treat) was 27.7% and 20.5% after preoperative CRT versus 16.5% and 6.5% after immediate surgery (HR 0.73; 95% CI 0.56 to 0.96; p = 0.025), which becomes an important evidence towards neoadjuvant approach in this group [32]. This study is not free from limitations.…”
Section: Discussionmentioning
confidence: 71%
“…Even though they didn't reach statistical signi cance in the primary endpoint that was overall survival, a signi cantly higher proportion of patients reached R0 resections in the neoadjuvant arm (71% vs 40%, P<0.001) and also a lower rate of perineural invasion [31]. In a posterior long-term analysis from this trial, three-and ve-year overall survival (intention-to-treat) was 27.7% and 20.5% after preoperative CRT versus 16.5% and 6.5% after immediate surgery (HR 0.73; 95% CI 0.56 to 0.96; p = 0.025), which becomes an important evidence towards neoadjuvant approach in this group [32]. This study is not free from limitations.…”
Section: Discussionmentioning
confidence: 71%
“…In the randomized phase II ALLIANCE A021501 trial, neoadjuvant chemotherapy followed by stereotactic radiotherapy has been investigated. In this trial, patients with BRPC were randomized between neoadjuvant extended chemotherapy (eight cycles of modified FOLFIRINOX) versus chemotherapy (seven cycles of modified FOLFIRINOX) followed by stereotactic radiotherapy (33)(34)(35)(36)(37)(38)(39)(40) Gy in 5 fractions) or hypofractionated radiotherapy (25 Gy in 5 fractions) (57). Recently, the results of an interim analysis were presented after enrollment of 126 patients.…”
Section: New Developments In Neoadjuvant Radiotherapymentioning
confidence: 99%
“…The PREOPANC trial randomized 246 patients with RPC or BRPC between neoadjuvant chemoradiotherapy and immediate surgery, both followed by adjuvant chemotherapy. In June 2021, the updated results were presented at the ASCO annual meeting ( 40 ). With a median follow-up of 59 months, a significant benefit in overall survival was found in patients treated with neoadjuvant treatment, with a 5-year overall survival (ITT) of 20.5% versus 6.5% in the patients treated with immediate surgery.…”
Section: Neoadjuvant Treatmentmentioning
confidence: 99%
“…The long-term results of the PREOPANC-1 trial, which is the first multicenter, randomized phase III trial investigating pre-operative chemoradiotherapy in PDAC, have been reported at the American Society of Clinical Oncology (ASCO) 2021 Meeting [72,73]. In this study, 246 patients with resectable PDAC or borderline resectable PDAC were randomly allocated to upfront surgery and adjuvant gemcitabine or pre-operative gemcitabine-based chemoradiotherapy (36 Gy in 15 fractions) and surgery followed by adjuvant gemcitabine.…”
Section: The Role Of Neo-adjuvant Chemoradiotherapymentioning
confidence: 99%